The Perspective of Puritan Moslem on the Family Planning Program: The Case of Salafimovement in Semarang, Central Java, Indonesia - Saratri Wilonoyudho1 , Lutfi Agus Salim2 , Ayis Muhtaram3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Family Planning Program is one of the policies in Indonesia related to the issue of population and familydevelopment that has been widely considered as successful. However, some obstacles emerged duringthe process of policy implementation, one of which was related to religious believes on family planning.An Islamic group called the Salafi Movement, for example, believes in pro-natalism and forbids the useof contraception. One of the sub-districts in the City of Semarang, called Banyumanik, has experienceda significant growth in the number of this group’s members. Using a qualitative approach with in-depthinterviews to collect data. Most members of this group have more than two children. Interestingly, manyof them hope to have many more children in the future. Most informants considered the Family Planningprogram is limited to control or restrict births using particular contraceptives. The value of the FamilyPlanning program challenged by the Salafi movement is related to the issue of limiting the number ofchildren. The government should extend the scope of the campaign, especially dialogues with them.